Impedance analysis of charge transfer upon nickel doping in Tio2-based flexible dye-sensitized solar cell - Abdullah H.; Mahalingam S.; Xian K.J.; Manap A.; Othman M.H.D.; Akhtaruzzaman M. (Springer Science and Business Media Deutschland GmbH, 2023)
Charge transfer; Costs; Nickel; Oxide minerals; Plastics industry; Temperature; Titanium dioxide; Electron lifetime; Electron recombinations; Flexible dye sensitized solar cell; Impedance analysis; Low-temperature fabrication; Mechanically robust; Plastic substrates; Temperature limitation; Dye-sensitized solar cells